Globalism and Local Democracy - Hambleton, R. author. aut Link
XVI, 258 p. 1 illus.
Keywords: This new book argues that cities and citizens are not helpless victims in a global flow of events. Three crucial questions are addressed through the three part structure: What is the nature of the globalization? What resulting challenges now confront cities and localities? How can local leaders respond to this changing environment in ways which strengthen local democracy? Written by leading urban scholars in Europe and North America the book draws on a range of disciplines to enhance academic understanding and illuminate lessons for policy and practice.